2010
DOI: 10.1519/jsc.0b013e3181b29614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static and Dynamic Stretching on Vertical Jump Performance in Collegiate Women Volleyball Players

Abstract: The purpose of this study was to determine the effect of stretching on peak jump height during a series of vertical jumps, specifically focusing on a) static stretching (SS), b) dynamic stretching (DS) and c) no stretching (NS) performed immediately before a series of countermovement vertical jumps (CMJ). Twelve female collegiate volleyball players (mean +/- SD; age 19.5 +/- 1.1 yr; height 1.71 +/- 0.06 m; mass 71.3 +/- 8.54 kg) volunteered for this study. Data collection lasted a total of 3 weeks, and each su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 21 publications
1
42
1
4
Order By: Relevance
“…Behm and Chaouachi (2011) reported a DS doseresponse effect in which greater overall peak force and power improvements were observed when >90 s (7.3% ± 5.3%) vs. <90 s (0.5% ± 2.3%) of DS was imposed immediately before testing. However, trivial ES or statistically nonsignificant performance changes were also elicited by both longer DS durations of 10 min (Needham et al 2009) and 15 min (Zourdos et al 2012) and by 180 repetitions , as well as by shorter durations, such as 45 s (Beedle et al 2008), 60 s (Samuel et al 2008), and 150 s (Amiri-Khorasani et al 2010), or 2 repetitions of 4 exercises (Dalrymple et al 2010). Hence, based on the variability among studies, it is difficult to demonstrate a dose-response relationship with DS.…”
Section: Dose-response Relationship For Dsmentioning
confidence: 97%
See 2 more Smart Citations
“…Behm and Chaouachi (2011) reported a DS doseresponse effect in which greater overall peak force and power improvements were observed when >90 s (7.3% ± 5.3%) vs. <90 s (0.5% ± 2.3%) of DS was imposed immediately before testing. However, trivial ES or statistically nonsignificant performance changes were also elicited by both longer DS durations of 10 min (Needham et al 2009) and 15 min (Zourdos et al 2012) and by 180 repetitions , as well as by shorter durations, such as 45 s (Beedle et al 2008), 60 s (Samuel et al 2008), and 150 s (Amiri-Khorasani et al 2010), or 2 repetitions of 4 exercises (Dalrymple et al 2010). Hence, based on the variability among studies, it is difficult to demonstrate a dose-response relationship with DS.…”
Section: Dose-response Relationship For Dsmentioning
confidence: 97%
“…Some studies do not report stretch intensity (Manoel et al 2008;Dalrymple et al 2010), but some report movement frequency (i.e., the number of dynamic movements per unit time) (Bacurau et al 2009;Fletcher 2010). Higher frequencies of DS and ballistic stretching (stretching using momentum in an attempt to exceed the normal ROM, which can include bouncing) may augment spindle reflex afferent excitation of the motor neurons and may theoretically affect subsequent performance (Matthews 1981).…”
Section: Effect Of Ds Movement Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by Bazett-Jones et al 8) , found that a decrease in vertical jump performance was shown after six weeks of static stretching training, but the decrease was not statistically significant. Dalrymple et al 20) examined whether different stretching protocols impacted the height of vertical jump. They found no significant differences between the SS, DS, and NS conditions for the jumps and suggested that individual responses were capable of differentiating vertical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Ke stejnému závěru dospěli i Dalrymple et al (2010). Jiné výsledky prezentují ve svých studiích Taylor, Sheppard, Lee a Plummer (2009) a La Torre et al (2010), jejichž závěrem je konstatování negativního vlivu statického strečinku na úroveň explozivní síly, respektive na výkony ve vertikálním skoku.…”
Section: ) Vliv Statického Strečinku Na Svalový Výkonunclassified